Adverse Childhood Experiences and Psychological Resilience among HIV Positive Youth in South Africa - Sigoda, Nozipho (University of the Witwatersrand, Johannesburg, 2024)
Research has revealed and highlighted the plight of HIV and its effects on individuals, their families and larger communities. Through a qualitative research approach, this study sought to explore the experiences of black South African Youth who are living with HIV and their exposure to Adverse Childhood experiences. Experiences of stigma, inequality and disparity were also explored. The research was largely informed by the resilience theory (Garmezy, 1978) which enabled the researcher to make sense of the participants’ experiences. The researcher then employed a non-probability purposive convenience sampling approach to recruit participants who were either born with HIV or contracted it while they were young. Interpretive Phenomenological Analysis (IPA) was then used to analyse the data that was derived from the semi-structured interviews conducted. Further, the use of IPA allowed the researcher to pay attention to the lived experiences of the participants. The themes extracted from this study suggest that children growing up with HIV in South Africa are often subjected to various adverse experiences that often challenge health and developmental outcomes. This is demonstrated by the dominant themes of navigating changes in identity, experiences of stigma, discrimination and marginalisation, exposure to poor socio-economic conditions and lastly resilience strategies employed to mitigate harm from the experiences.
A research report Submitted in fulfillment of the requirements for a Master of Arts by Coursework and Research Report in Psychology, In the Faculty of Humanities , School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Childhood Adverse Experiences; ACES; Lived Experiences; Resilience; Youth; SDG-3: Good health and well-being